AUDIT MANAJEMEN SEBAGAI SARANA UNTUK MENILAI EFEKTIVITAS SUMBERDAYA MANUSIA DI BANK SYARIAH BUKOPIN - Ahyakudin Ahyakudin (FEB Universitas Sultan Ageng Tirtayasa, 2017)
Implementation of human resource audit requires maximum accuracy, because it concerned with the interests of the people. Human Resource Management is as the utilization, development, assessment, rewarding services and management of individual members of the organization or group work. The formulation of the problem as follows: What is the role of HR audits in Bank Syariah Bukopin in improving effectiveness What are the HR audit programs, What are the problems or constraints faced by personnel managers in HR audits, how the process of recruitment in Bank Syariah Bukopin, whether running efisein . Audit discussion conducted: Human Resource Planning, Human Resource Recruitment and Selection, Human Resources Performance Appraisal, Human Resources Career Training and Development, Human Resource Performance Assessment. The conclusion that management audit as a means of effectiveness of Human Resources in Bank Syariah Bukopin run effectively.